Assessing ontogenetic maturity in extinct saurian reptiles. (2nd December 2020) - Griffin, Christopher T.; Stocker, Michelle R.; Colleary, Caitlin; Stefanic, Candice M.; Lessner, Emily J.; Riegler, Mitchell; Formoso, Kiersten; Koeller, Krista; Nesbitt, Sterling J.
ABSTRACT: Morphology forms the most fundamental level of data in vertebrate palaeontology because it is through interpretations of morphology that taxa are identified, creating the basis for broad evolutionary and palaeobiological hypotheses. Assessing maturity is one of the most basic aspects of morphological interpretation and provides the means to study the evolution of ontogenetic changes, population structure and palaeoecology, life‐history strategies, and heterochrony along evolutionary lineages that would otherwise be lost to time. Saurian reptiles (the least‐inclusive clade containing Lepidosauria and Archosauria) have remained an incredibly diverse, numerous, and disparate clade through their ~260‐million‐year history. Because of the great disparity in this group, assessing maturity of saurian reptiles is difficult, fraught with methodological and terminological ambiguity. We compiled a novel database of literature, assembling >900 individual instances of saurian maturity assessment, to examine critically how saurian maturity has been diagnosed. We review the often inexact and inconsistent terminology used in saurian maturity assessment (e.g. 'juvenile', 'mature') and provide routes for better clarity and cross‐study coherence. We describe the various methods that have been used to assess maturity in every major saurian group, integrating data from both extant and extinct taxa to give a full account of the current state of the field and providing method‐specific pitfalls, best practices, and fruitful directions for future research. We recommend that a new standard subsection, 'Ontogenetic Assessment', be added to the Systematic Palaeontology portions of descriptive studies to provide explicit ontogenetic diagnoses with clear criteria. Because the utility of different ontogenetic criteria is highly subclade dependent among saurians, even for widely used methods (e.g. neurocentral suture fusion), we recommend that phylogenetic context, preferably in the form of a phylogenetic bracket, be used to justify the use of a maturity assessment method. Different methods should be used in conjunction as independent lines of evidence when assessing maturity, instead of an ontogenetic diagnosis resting entirely on a single criterion, which is common in the literature. Critically, there is a need for data from extant taxa with well‐represented growth series to be integrated with the fossil record to ground maturity assessments of extinct taxa in well‐constrained, empirically tested methods.